2020
DOI: 10.31557/apjcp.2020.21.5.1339
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Attitudes toward Breast Cancer Screening among Omani Women

Abstract: Background: Breast cancer (BC) is the most common cancer accounting for 24.5% of Omani female cancer. Early detection of BC through regular breast cancer screening (BCS) has been found to decrease mortality rates. The aim of this study was to identify knowledge, attitudes and barriers of Omani women toward BCS. Methods: A cross-sectional study was conducted among adult Omani women attending the Sultan Qaboos University Hospital (SQUH). Results: A total of 358 Omani women participated from 420 invited (response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 33 publications
7
30
2
3
Order By: Relevance
“…While the majority of women had a positive attitude towards BC screening in the present study, the majority of women in the study by Al-Azri in Oman did not have a positive attitude towards BC screening (12). In Heena's study, more than half of the participants believed that they could not be diagnosed by BC screening (28).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…While the majority of women had a positive attitude towards BC screening in the present study, the majority of women in the study by Al-Azri in Oman did not have a positive attitude towards BC screening (12). In Heena's study, more than half of the participants believed that they could not be diagnosed by BC screening (28).…”
Section: Discussioncontrasting
confidence: 65%
“…Women in the Middle East face a number of psychosocial, cultural, and doctrinal challenges that lead to a negative attitude toward screening, resulting in delays in the diagnosis of BC and an increased risk of death (12). A closer look at women's knowledge and attitudes is useful to better understand how they decide whether or not to participate in BC screening (13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported similar findings. 15 25 Although a large proportion of women in this study were able to recognise that lumps in the breast or armpit were a possible symptom of BC, the majority were not aware of other symptoms such as fatigue, unexplained weight loss or loss of appetite. Indeed, less than half of the women reported having been aware of or knowledgeable regarding BC prior to their own diagnosis.…”
Section: Discussionmentioning
confidence: 84%
“…The patients who are cured of cancer follow in an outpatient clinic as per protocol and long-term survivors are followed in survivorship clinics or shifted to tertiary/primary care. A dedicated palliative care team is there for pain management, palliative symptom care, and end-of-life care once the patient is transited to palliative symptomatic care [18,19].…”
Section: Multi-sectoral Efforts To Prevent and Control Cancermentioning
confidence: 99%
“…A cancer colon and Hepatocellular screening in susceptible population groups is evolving. A comprehensive Genetic center is recently established under MoH where tests and genetic counseling services are available for hereditary and familial cancers [18].…”
Section: Cancer Screening Programsmentioning
confidence: 99%